2012
DOI: 10.1111/j.1469-5812.2009.00555.x
|View full text |Cite
|
Sign up to set email alerts
|

The Complicated Conversation of Class and Race in Social and Curricular Analysis: An examination of Pierre Bourdieu's interpretative framework in relation to race

Abstract: As a means to challenge and diminish the hold of mainstream curriculum's claim of being a colorblind, politically neutral text, we will address two particular features that partially, though significantly, constitute the hidden curriculum in the United States—race and class—historically studied as separate social issues. Race and class have been embedded within the institutional curriculum from the beginning in the US; though rarely acknowledged as intertwined issues. We illustrate how the theoretical and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Employers likewise may not have been conscious of the fact that their employment preferences were based in race. As a result of the entrenched ideology surrounding mestiçagem, Brazilians often misrecognize racial ideologies and discourses as social facts rather than sources of domination and oppression, thus normalizing social inequality (McKnight and Chandler 2012).…”
Section: Discussion: Symbolic Power In Brogodó's Touristscapementioning
confidence: 99%
See 1 more Smart Citation
“…Employers likewise may not have been conscious of the fact that their employment preferences were based in race. As a result of the entrenched ideology surrounding mestiçagem, Brazilians often misrecognize racial ideologies and discourses as social facts rather than sources of domination and oppression, thus normalizing social inequality (McKnight and Chandler 2012).…”
Section: Discussion: Symbolic Power In Brogodó's Touristscapementioning
confidence: 99%
“…Studies of social inequality reveal that the accrual of cultural capital and its socioeconomic benefits are mediated not only by class, as Bourdieu emphasized, but by race and ethnicity as well (Lan 2011;McKnight and Chandler 2012;Purcell 2007;Yosso 2005), thus exposing the economic and social consequences of someone's inability to attain cultural capital (Carter 2003) and to embody a habitus that reflects cultural capital. In Brazil, habitus is racialized, and a habitus that includes embodied cultural capital indexes someone's whiteness.…”
Section: Cultural Capital Symbolic Capital and The Study Of Race Anmentioning
confidence: 99%
“…A third philosopher, who brings the notion of symbolic violence to the discussion, is the sociologist Pierre Bourdieu. His concepts of field, cultural capital and habitus are central to post-structural education theory, and have much to contribute to an understanding of the ways in which PACS education might itself symbolically reproduce violence (Bourdieu, 1977;Bourdieu & Passeron, 1986McKnight & Chandler, 2009).…”
Section: Reclaiming Pacs Education Through Second Order Reflexivitymentioning
confidence: 99%
“…The discrimination and systematic oppression of people of color persist even though some curriculum within higher education has become inclusive of race, class, and gendered perspectives. McKnight and Chandler (2012) found that "institutional versions of curriculum are predisposed toward anti-democratic education because they tend to marginalize or entirely exclude the voices of the 'other' by way of privileging and socially reproducing the patriarchal, white normative perception of the world" (p. 4475). This lack of democracy within curriculum perpetuates the silencing of diverse voices.…”
Section: Anglocentric Inclinations: a Historically Biased Curriculummentioning
confidence: 99%